The Development of Chinese Novice University English Teachers’ Professional Identity in Interaction: A Multimodal (Inter)action Analysis - Zhou, Jing (Auckland University of Technology, 2026)
Over the past two decades, teacher identity has attracted increasing scholarly attention, particularly in teacher education and professional development. However, the complex processes underpinning novice teacher identity formation remain underexplored. To address this gap, this thesis presents a longitudinal multi-case study of four novice EFL teachers in China, observed across one academic semester. The study employs a Multimodal (Inter)action Analysis (MIA) framework (Norris, 2004, 2011, 2019). Drawing on three rounds of video-recorded classroom observations and semi-structured interviews conducted throughout the semester, the study examines how identity is constructed across interactional, institutional, and sociocultural dimensions. This doctoral research is presented in a thesis-by-publication format, comprising three published articles (Articles I–III). Collectively, the research captures how novice EFL teachers negotiate personal aspirations and institutional demands through both discourse and embodied action. Article I explores the identity struggles of one teacher (Caroline), revealing tensions between her imagined ideals of relaxed, student-centred teaching and the realities of exclusion and resistance within a high-power-distance institutional culture. Multimodal analysis highlights the emotional labour and adaptive identity work required for professional integration. Article II follows two novice teachers, Mandy and Yable, as they transition from textbook-centred delivery to a more student-centred, interactive pedagogy. By analysing changes in multimodal resources—such as gaze, gesture, and vocal modulation-the study shows how embodied communication facilitates pedagogical innovation and identity empowerment. Article III examines how four early-career lecturers navigate the competing demands of teaching and research under intensified “publish-or-perish” pressures. Divergent identity trajectories are identified: some participants resist institutional pressures to maintain teaching-oriented identities, while others strategically integrate research commitments into their professional self-concept. Multimodal analyses reveal how identity work is negotiated not only through language but through bodily enactments within academic communities. Together, the findings illustrate that novice EFL teacher identity development is a dynamic, multimodally mediated process shaped by discursive, relational, and institutional forces. The thesis advocates for teacher education and higher education policies that recognise the embodied dimensions of professional identity work, foster emotional resilience, and support more integrated models of teaching and research engagement. These insights aim to inform sustainable professional development strategies for novice educators, with implications extending beyond China to other international contexts.